Efektivitas Tumbuhan Sungkai (Albertisia papuana Becc) Suku Dayak Ngaju Untuk Menurunkan Gula Darah Pada Tikus Putih (Rattus norvegicus) - Dery Ade Pramana (Jurnal Kesehatan Indonesia, 2025)
Diabetes mellitus (DM) is a chronic disease characterized by blood glucose levels exceeding normal. One alternative treatment can use herbal plants or natural ingredients that have the potential as a source of antioxidants. Sungkai plants are one of the plants used by the Dayak Tribe for generations to treat DM. The purpose of this study was to determine whether each organ of the sungkai plant has the potential as a DM drug. The parameters of this study consisted of the antioxidant activity content and the effectiveness of the sungkai plant as a DM drug. This study is a type of experimental research, the data obtained will be analyzed statistically using Anova with sequence, normality test, homogeneity and further test using the Duncan test. The results obtained showed that the antioxidant activity content of the sungkai plant organs had differences in the antioxidant activity content of each organ, significantly different (P<0.05) and the sungkai plant has hypoglycemic compounds characterized by a consistent decrease in glucose levels from high to low, thus showing a significant difference (P<0.05). This study is expected to have a good impact on diabetes sufferers so that it can reduce the impact and excessive use of patented drugs.